2014
DOI: 10.2149/tmh.2013-27
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Potential of Variant Clones of the Oshima Strain of Far-Eastern Subtype Tick-Borne Encephalitis Virus

Abstract: Tick-borne encephalitis virus (TBEV) is a zoonotic agent that causes acute central nervous system (CNS) disease in humans. We previously suggested that immune response in addition to CNS infection contribute to mouse mortality following TBEV infection. However, we did not examine the influence of virus variants in the previous study. Therefore, in this study, we investigated the biological and pathologic potentials of the variant clones in the TBEV Oshima strain. We isolated eight variant clones from the stock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…TBEV is known to exist as clusters of quasispecies within ticks and mammals783839. Quasispecies populations are influenced by the host environment, and changes in the population might affect the phenotype of specific strains40.…”
Section: Discussionmentioning
confidence: 99%
“…TBEV is known to exist as clusters of quasispecies within ticks and mammals783839. Quasispecies populations are influenced by the host environment, and changes in the population might affect the phenotype of specific strains40.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, other factors contributing to disease severity have been shown besides the host-dependent risk factors, such as the virulence of the particular strain, which could be inconsistent with the TBEV subtype [32] , the inoculation dose [33] , and the immunomodulatory compounds of tick saliva inoculated with virus into the skin [4] . Animal models are also commonly used to elucidate the mechanism of disease development following TBEV infection in vivo and suggest that CNS pathology during TBE is primarily driven by immune response and inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic potential of variant clones of the Oshima strain of Far-Eastern subtype of TBEV was analyzed in a separate study. It was shown that an amino acid substitution of Glu122 → Gly in the E protein could have affected virus infection and replication in vivo, as well as the attenuated pathogenicity in mice [ 79 ].…”
Section: Discussionmentioning
confidence: 99%